2022
DOI: 10.1186/s13065-022-00814-0
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical study for removal of trimethoprim from wastewater using organically modified silica with pyrazole-3-carbaldehyde bridged to copper ions

Abstract: Background Human and veterinary antibiotics are typically discharged as parent chemicals in urine or feces and are known to be released into the environment via wastewater treatment plants (WWTPs). Several research investigations have recently been conducted on the removal and bioremediation of pharmaceutical and personal care products (PPCPs) disposed of in wastewater. Results SiNP-Cu, a chelating matrix, was produced by delaying and slowing 1.5-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 60 publications
2
3
0
Order By: Relevance
“…These results, which are substantiated in references, add substantially to our understanding of the behavior and attributes of the system under the conditions we simulated. 66 , 68 , 77 , 78 Moreover, computation of the relative concentration of MB (methylene blue) on the respective surfaces, as illustrated in Figure 16 b, lends additional support to our findings. This analysis reveals a notable affinity of MB molecules for the surfaces, demonstrating their effective adhesion.…”
Section: Results and Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These results, which are substantiated in references, add substantially to our understanding of the behavior and attributes of the system under the conditions we simulated. 66 , 68 , 77 , 78 Moreover, computation of the relative concentration of MB (methylene blue) on the respective surfaces, as illustrated in Figure 16 b, lends additional support to our findings. This analysis reveals a notable affinity of MB molecules for the surfaces, demonstrating their effective adhesion.…”
Section: Results and Discussionsupporting
confidence: 79%
“…Our confidence in the accuracy of the data we’ve collected and in the validity of the observations we’ve made, thanks to the small temperature swings we’ve seen, is further bolstered by the fact that they’re consistent with the simulation’s predictions, as shown in the supporting refs ,, . These results, which are substantiated in references, add substantially to our understanding of the behavior and attributes of the system under the conditions we simulated. ,,, Moreover, computation of the relative concentration of MB (methylene blue) on the respective surfaces, as illustrated in Figure b, lends additional support to our findings. This analysis reveals a notable affinity of MB molecules for the surfaces, demonstrating their effective adhesion.…”
Section: Results and Discussionsupporting
confidence: 74%
“…Both studies reported that the main adsorption driving force was the electrostatic interaction between the anionic surface charge of the respective drugs and the protonated adsorbent surface. Besides, Jodeh et al (2022) recorded high adsorptive capacity while adsorbing trimethoprim onto a chelating matrix synthesized via a reaction between 1.5-dimethyl-1H-pyrazole-3-carbaldehyde, 3-aminopropyltrimethoxysilane and silica gel. According to the study, efficient drug binding occurred via complexation between the nitrogen atoms of the adsorbent and π-electrons originating from the benzene and pyrimidine rings in the drug.…”
Section: Silicamentioning
confidence: 99%
“…According to the study, efficient drug binding occurred via complexation between the nitrogen atoms of the adsorbent and π-electrons originating from the benzene and pyrimidine rings in the drug. Also, low adsorption enthalpy values were recorded throughout the entire sorption process due to the hydrogen bond formation and the formation of a water bridge between the nitrogen/oxygen-containing groups of the trimethoprim and the amine groups of the adsorbent (Jodeh et al 2022). Dipyridyl-based organo-silica nanosheets were successfully synthesized and utilized for adsorbing clofibric acid, ketoprofen, and naproxen sodium from wastewater (Guo et al 2020).…”
Section: Silicamentioning
confidence: 99%
“…Jodeh et al 2022). The energies of the HOMO and LUMO frontier orbitals and the gap energy of the molecules calculated by the DFT/B3LYP 6-31 + G (d,p) method under different pH conditions from the optimized structures are given in Table6, a unprotonated and protonated state.…”
mentioning
confidence: 99%